Prevalence, antibiotic susceptibility and characterization of antibiotic resistant genes among carbapenem-resistant Gram-negative bacilli and yeast in intestinal flora of cancer patients in North Lebanon - Rima Christophy; Marwan Osman; Hassan Mallat; Marcel Achkar; Azzam Ziedeh; Walid Moukaddem; Fouad Dabboussi; Monzer Hamze (Elsevier, 2017)
The emergence and spread of carbapenem-resistant bacteria are a significant clinical and public health concern. The aim of the study is to determine the prevalence of intestinal carriage of carbapenem-resistant bacteria and yeasts in cancer patients under chemotherapy. 41 stool samples collected from cancer patients in Nini hospital in Tripoli, North Lebanon have been analyzed. After isolating yeasts and carbapenem-resistant bacteria, a biochemical identification and antimicrobial susceptibility profile were determined. The mechanism of enzymatic carbapenem-resistance was detected by searching for carbapenemases by both Hodge test and PCR assays. The association of several mechanisms of resistance was also searched. 46.3% (19/41) of patients were colonized by yeast. Candida glabrata (6/19) was the major species. The prevalence of carbapenem-resistant bacteria was 24.4% (10/41) including Escherichia coli (5/10), Enterobacter cloacae (1/10), Enterobacter aerogenes (1/10) Edwardsiella hoshinae (1/10) Pantoea agglomerans (1/10) and Pseudomonas stutzeri (1/10). PCR and sequencing of the amplified fragments revealed that Pseudomonas stutzeri (1/1) carried VIM gene and Enterobacter aerogenes (1/1) and E. coli (1/5) carried OXA-48 gene. The other Enterobacteriaceae were resistant to carbapenems by mechanisms other than a carbapenemase including hyperproduction of cephalosporinase (4/10), extended spectrum beta-lactamases (1/10) and both cephalosporinase and extended spectrum beta-lactamases (2/10). High prevalence of intestinal carriage of carbapenem-resistant bacteria and yeasts were detected in cancer patients under chemotherapy. In order to prevent the development of endogenous infection and the dissemination of antimicrobial resistance, an implementation of antibiotic stewardship programs and infection control measures is required in hospitals particularly in the department of chemotherapy. Keywords: Cancer, Yeasts, Carbapenemases, Multidrug resistant bacteria, Colonization